Angioleiomyoma of the Ankle - Kasman, Uğur Onur; Korkmaz, Özgür; Çeçen, Gültekin Sıtkı; Rodop, Osman; Karadayı, A. Nimet (Cerrahpaşa Medical Journal, 2022)
Leiomyoma is a benign soft-tissue mass of smooth muscle origin. Patients usually present to the outpatient clinic with a slow-growing subcutaneous soft-tissue mass. It was aimed to report that angioleiomyoma can be rarely localized around the ankle. A 54-year-old male patient was admitted to our outpatient clinic with a complaint of soft-tissue mass with periodic pain on the lateral side of the left ankle for 1 year. After clinical and radiological evaluation, a 22 mm × 18 mm septated soft-tissue mass that did not show any contrast was detected on magnetic resonance imaging. Soft-tissue mass excision was planned with extracapsular resection against the possibilities of malignant pathology. The soft-tissue mass was approximately 2 × 1.5 cm in size, and it was regularly encapsulated. Pathological examination results were determined as vascularized leiomyoma. Vascularized leiomyoma should be considered in the differential diagnosis of ankle soft-tissue tumors, and it should be excised with wide margins. Cite this article as: Kasman UO, Korkmaz Ö, Çeçen GS, Rodop O, Karadayı AN. Angioleiomyoma of the ankle. Cerrahpaşa Med J. 2022;46(3):275-277.